Architectural Frameworks for Master Data Management (MDM): Enabling Holistic Customer and Product Master Synchronization in Investment Portfolios - Inala, Ramesh (International Journal of Scientific Research and Management (IJSRM), 2021)
Master Data Management (MDM) is a critical discipline for enterprise architecture. MDM is ubiquitous and multi-sourced. It spans and integrates systems and data domains, working closely with Business Process Management (BPM). It is the prerequisite of Business Intelligence (BI), and of business derived from the dynamics of the digital universe and from rich Data Lakes. It asks, and answers, unique questions about the business. For a robust MDM implementation, the discipline needs to be backed with an overarching MDM framework that engages business and IT. Such an MDM architectural framework is incomplete without the architecture of systems connected to master data, and the pivotal role of these systems in the business process. We explore ideas and insights behind the MDM architectural frameworks, and related questions the frameworks answer.Master data is a specialized class of data of any business entity for an organization, the context in which the business entity exists, the why pertaining to the business entity. Within a business, it is core and is at the heart of the business process architecture. Data integration and consistency is a primary goal of data management. The objective of MDM is to establish a single version of the truth of integrated master data that is made available in a consistent manner to multiple consumers, internal or external to the organization. MDM is the act of creating and maintaining a master brownstone. MDM requests this silos view and develops it further with a multi-silo and multi-replication perspective to build the integration framework for a given enterprise. MDM is the responsibility of the business people owning the process, but working with the IT organization or a third-party vendor to implement the physical data structure and make it available to the users.